(untitled) (Scientific journal of the Fergana State University, 2023)
In this article I consider whether communicative and collaborative approaches in language teaching on the bases of proverbs and sayings will lead to better results in language learning. This article examines these objectives in three secondary schools located in Ferghana valley. Our qualitative methodology included, firstly interviews with teachers, pupils, and administrators, secondly, classroom observations, review of text books and school documents, and, finally surveys of both teachers and pupils in the three secondary schools. We found that organizing collaborative way of learning English with a help of proverbs and sayings will lead to develop communicative competence of the learners.